SYSTEM ADMINISTRATION DATA COLLECTION RT012 PINANG RANTI USING VISUAL BASIC 6.0 - Mohammad Irfan; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2005)
Science and computer technology is now increasingly sophisticated and rapidly spreading, so it is very helpful in the process of transferring data still use manual systems. certainly be very useful and more effective and efficient in time and effort, if the data collection activities on the environment Neighborhood residents (RT) can be done with a computerized system.In this context the authors are interested in making an administrative program design a computerized data collection on citizens. And discuss also about the Data Flow Diagrams (DFD), Entity Relationship Diagram (ERD), Normalization, and the appearance of the program Visual Basic 6.0.